Объяснение:
4b²-(7b²-3bc)+(3b²-7bc)=4b²-7b²+3bc+3b²-7bc=-4bc
-4bc=-4(-1,5)*4=24
6х(6х-4)+9х(3-4х)=36х²-24х-27х-36х²=-51х
-51х=-51(-1)=51
(х+2)(х-5)-(х-3)(х+4)=х²+2х-5х-10-х²+3х-4х+12=-4х+2
-4х+2=-4(-5,5)+2=24
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Объяснение:
4b²-(7b²-3bc)+(3b²-7bc)=4b²-7b²+3bc+3b²-7bc=-4bc
-4bc=-4(-1,5)*4=24
6х(6х-4)+9х(3-4х)=36х²-24х-27х-36х²=-51х
-51х=-51(-1)=51
(х+2)(х-5)-(х-3)(х+4)=х²+2х-5х-10-х²+3х-4х+12=-4х+2
-4х+2=-4(-5,5)+2=24